Asthma, Allergy and Eczema among Adults in Multifamily Houses in Stockholm (3-HE Study) - Associations with Building Characteristics, Home Environment and Energy Use for Heating - Norbäck, Dan; Lampa, Erik; Engvall, Karin (PloS one, 2014)
Risk factors for asthma, allergy and eczema were studied in a stratified random sample of adults in Stockholm. In 2005, 472 multifamily buildings (10,506 dwellings) were invited (one subject/dwelling) and 7,554 participated (73%). Associations were analyzed by multiple logistic regression, adjusting for gender, age, smoking, country of birth, income and years in the dwelling. In total, 11% had doctor's diagnosed asthma, 22% doctor's diagnosed allergy, 23% pollen allergy and 23% eczema. Doctor's diagnosed asthma was more common in dwellings with humid air (OR = 1.74) and mould odour (OR = 1.79). Doctor's diagnosed allergy was more common in buildings with supply exhaust air ventilation as compared to exhaust air only (OR = 1.45) and was associated with redecoration (OR = 1.48) and mould odour (OR = 2.35). Pollen allergy was less common in buildings using more energy for heating (OR = 0.75) and was associated with humid air (OR = 1.76) and mould odour (OR = 2.36). Eczema was more common in larger buildings (OR 1.07) and less common in buildings using more energy for heating (OR = 0.85) and was associated with water damage (OR = 1.47), humid air (OR = 1.73) and mould odour (OR = 2.01). Doctor's diagnosed allergy was less common in buildings with management accessibility both in the neighbourhood and in larger administrative divisions, as compared to management in the neighbourhood only (OR = 0.49; 95% CI 0.29-0.82). Pollen allergy was less common if the building maintenance was outsourced (OR = 0.67; 95% CI 0.51-0.88). Eczema was more common when management accessibility was only at the division level (OR = 1.49; 95% CI 1.06-2.11). In conclusions, asthma, allergy or eczema were more common in buildings using less energy for heating, in larger buildings and in dwellings with redecorations, mould odour, dampness and humid air. There is a need to reduce indoor chemical emissions and to control dampness. Energy saving may have consequences for allergy and eczema. More epidemiological studies are needed on building management organization.